Optical soliton generation in fiber optics : free & forced nonlinear schrodinger equation - Kee, Boon Lee (2013)
Future telecommunication will depend on effective data transmission, high quality video encoding, and efficient networking using optical solitons in fiber optic. At this moment, we encounter slow data transmission, fiber loss and chromatic dispersion that can be considered as forcing terms. Fiber optics is a man-made tool that has changing refractive index and this cause fiber loss. Nonlinear Schrödinger (NLS) equation which is a nonlinear partial differential equation can models the non-forced system effectively that combines the effect of nonlinearity and dispersion. In this research, a numerical method that consists of semi-implicit Pseudo-Spectral method scheme will be implemented to solve NLS equation. Comparing the results from analytical solution between numerical solution of NLS equation to determine an accurate and stable code so that it can be used to solve forced nonlinear Schrödinger (fNLS) equation that models forcing system. MATLAB computer programming which is user friendly will be used to implement the numerical scheme that produces various graphical outputs to simulate the propagation of solitons.